2013
DOI: 10.1016/j.jclinepi.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

What is the effect of area size when using local area practice style as an instrument?

Abstract: Many researchers have used local area practice style measures as instruments in instrumental variable analysis. What constitutes the size of a “local area” for measuring practice styles may affect the strength of the relationship between the instrument and treatment choice, and whether the instrument is related to unmeasured confounding factors. Among previous studies using local area practice style measures as instruments, only two reported whether their estimates were robust to changes in the local area size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…As such, ATRs provide an adjusted measure of a local area’s “adjuvant treatment signature.” The ATR method has been used successfully in previous studies of geographic treatment variation and comparative effectiveness, along with methodological papers aimed at better understanding estimates of treatment effectiveness from observational studies with unmeasured confounding [4147]. A summary of the method is outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…As such, ATRs provide an adjusted measure of a local area’s “adjuvant treatment signature.” The ATR method has been used successfully in previous studies of geographic treatment variation and comparative effectiveness, along with methodological papers aimed at better understanding estimates of treatment effectiveness from observational studies with unmeasured confounding [4147]. A summary of the method is outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with previous research assessing the effect of area size when using local area practice style as an instrument. 223 Brooks et al showed that using larger local areas to measure practice styles generate less treatment variation (larger Chow-F values) with larger standard errors of treatment estimates. 223 Brooks et al also suggested that use of larger area sizes may mitigate the bias that local area practice style might be related to ecological factors within smaller areas (e.g.…”
Section: Area Diagnosis Ratios As Instrumentsmentioning
confidence: 99%
“…neighborhood cultural and behavioral factors). 223 However, it is been argued that physician practice styles around individual ZIP codes might have little in common in too large local areas. 96 Therefore, we tested the robustness of our IV models based on instruments of local depression diagnosing styles across different sizes with the minimum number of patients varying from 50 to 200 persons around each ZIP code (Appendix 1-39).…”
Section: Area Diagnosis Ratios As Instrumentsmentioning
confidence: 99%
“…Observed geographic variation in rates of ACE/ARB treatment suggests that prescribing of ACE/ARBs may be sensitive to the beliefs, preferences, or practice styles of physicians across areas. [85][86][87] This geographic variation forms the foundation for our instrumental variables analysis. A theoretical model for the factors likely to be affecting decision to use ACE/ARBs, the effectiveness of ACE/ARBs, and survival for patients with AMI is described below.…”
Section: Empirical Applicationmentioning
confidence: 99%
“…88 94 Following the findings of previous work exploring the validity of ATRs as instruments in this clinical setting, instrumental variables will be defined in this study using a threshold of 150 patients to create local areas. 87 Area treatment ratios (ATRs) will be calculated for each zip codedefined local area as the ratio of the number of patients observed to have received an ACE/ARB after AMI over the sum of the estimated probabilities of these patients receiving an ACE/ARB after AMI. Predicted ACE/ARB probabilities will be generated using a multivariate logistic model of ACE/ARB receipt across all patients in the analytical sample.…”
Section: Theoretical Modelmentioning
confidence: 99%